Dental ceramic prostheses by stereolithography-based additive manufacturing: potentials and challenges. (17th February 2019) - Li, Hezhen; Song, Lu; Sun, Jialin; Ma, Jing; Shen, Zhijian
ABSTRACT: The current method for making dental ceramic prostheses in a subtractive manner causes a severe waste of materials while requires excessive manual works that bring in the uncertainty for control of quality. The rapid development and commercialisation of additive manufacturing (AM) has aroused interest and wonders both in material and dental communities about their potentials and challenges in fabricating of ceramic prostheses in a materials-saving manner. In this work, AM approach was applied to fabricate the dental bridges and implants made of zirconia. The achieved geometries and dimensional accuracy are used to demonstrate the potential of this technique in fabricating of dental ceramic prostheses, whereas the observed macro and micro defects formed during the treatment process is used to reveal the challenges facing in order to adapt this technology into real dental practice. Suggestions are provided for future development of the technology, particularly on minimising the processing defects.